G_ab = R_ab - 1/2 * R * g_ab(adsbygoogle = window.adsbygoogle || []).push({});

and

R = g^(ab) * R_ab

then

G_ab = R_ab - 1/2 * R_ab * (g^(ab) * g_ab)

=1/2 * R_ab

for this abomination someone please correct me.

**Physics Forums | Science Articles, Homework Help, Discussion**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Einstein Tensor

Loading...

**Physics Forums | Science Articles, Homework Help, Discussion**